Population genetic structure in wild and hatchery populations of white cloud mountain minnow (Tanichthys albonubes): Recommendations for conservation. (October 2015) - Luo, Jin-Zhen; Lin, Hung-Du; Yang, Fei; Yi, Zu-Sheng; Chan, Bosco-Puilok; Zhao, Jun
Abstract: We used mitochondrial (mt) cytochrome b gene (cyt b ) to compare the genetic variability in three hatchery broodstocks of white cloud mountain minnow with the variability in six wild populations sampled in two river drainages. A total of 43 haplotypes in 102 specimens were observed, with no haplotype shared between wild and hatchery populations. The nucleotide diversity of the wild samples (0.048) was significantly higher than that of the hatchery ones (0.007), but the haplotype diversity was almost similar between them. Two major phylogenetic haplotype groups were revealed and estimated to diverge about 6.531 myr (million years) ago. Significant genetic differentiation was revealed between wild and hatchery populations as well as among nine sampled populations, suggesting at chance effect during the founding process for the hatchery population and a subsequent genetic drift. According to the network, the connection between wild and hatchery populations indicates that present hatchery populations originated from single wild population. We suggested that two regions (Pearl River system and Lu River) identified by reciprocal mtDNA monophyly and SAMOVA should be regarded as three different ESUs and two different MUs in South China, respectively. Highlights: We present phylogeographical analyses in three hatchery and six wild populations of Tanichthys albonubes in South China. According to the network, the connection indicates that present hatchery populations originated from single wild population. We suggest that two regions (Pearl River drainage and Lu River) identified by SAMOVA should be regarded as two different management units (MUs).